Evidence of crustal growth during the Svecofennian orogeny : New isotopic data from the central parts of the Paleoproterozoic Central Finland Granitoid Complex - Heilimo, Esa; Mikkola, Perttu; Ahven, Marjaana; Huhma, Hannu; Lahaye, Yann; Virtanen, Ville J. (Precambrian Research, 2023)
Peer reviewed